WWII battlefront ([St. Laurent, Quebec : Madacy Home Video, 2004)
A review of the battles of World War II using colorized newsreel footage and films
vol. 1. Atlantic Campaign: Operation dragoon (Aug 1944), Battle of the Bulge (Dec 1944) and Pacific Campaign: The last stronghold (Nov 1944), Mount Hot Rocks (Feb 19, 1945) (Dec 1944) .- vol. 2. The Atlantic campaign (Part 1): Dunkirk (Sept. 1, 1939), the battle of Norway (early, 1940), the bombing of England (fall, 1940), the battle of Malta (June, 1941). - vol. 3. The Atlantic campaign (Part 2): North Africa (Nov.1942), Monte Cassino (Sept.3, 1943), D-Day (June 6, 1944), retaking France (6 weeks after D-Day). - vol. 4. The Pacific campaign (Part 1): The fall of Singapore (Oct. 1941), Pearl Harbor (Dec 7, 1941), the battle of midway (June 2, 1942), the Solomon Island ()July, 1942. - vol. 5. The Pacific campaign (Part 2): the Gilbert Islands (Nov. 1943), Burma-The forgotten Front (Spring, 1943), battle in Pulau (Summer, 1944), liberation of the Philippines
Title from container
Features: animated menus, battlefront previews, military medals slideshow, original newsreels from the war years, biographical documentaries, direct scene access
DVD format
Dolby digital
With optional English or Chinese subtitles
Keywords: World War, 1939-1945 -- Campaigns; World War, 1939-1945; Wars